Pengaruh Budaya Organisasi Terhadap Kinerja Melalui Motivasi di Sekretariat Daerah Kabupaten Aceh Utara - Yusniar Yusniar (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2016)
The purpose of this study was to look at the effect of organizational culture on motivated mediated performance, this study used quantified qualitative data. To analyze the data, used path analysis by using multiple linear regression and motivation into mediation variable. The number of respondents used is 100 local secretariat apparatus in North Aceh district. The result of the research shows that organizational culture has an effect on the apparatus performance motivation, and also organizational culture have an effect on to performance, motivation also directly influence to performance, motivation also mediate between organizational culture and apparatus performance of secretariat of regency of north Aceh regency.Keywords: Organizational Culture, Motivation, Performance